The Neuroprotective Effects of Astragaloside IV against H2O2-Induced Damage in SH-SY5Y Cells are Associated with Synaptic Plasticity - Zurong Song; Ali Tao (Journal of Chemistry)
The aim of this study was to investigate whether the neuroprotective effects of astragaloside IV (AS-IV) against hydrogen peroxide (H2O2)-induced damage on human neuroblastoma cell line (SH-SY5Y) are associated with synaptic plasticity. The concentration screening of AS-IV and H2O2 on SH-SY5Y cells and the protective effects of AS-IV on SH-SY5Y cells under H2O2 stress were all determined by MTT assay. The expression of postsynaptic density 95 (PSD-95) and growth-associated protein 43 (GAP-43) were measured by western blot (WB) and inmunofluorescence staining assay under the same treatment conditions. According to the MTT results, the concentration of H2O2 at 50 μmol/L for 3 h was used for the cell damage model, and various concentrations of AS-IV (0.1, 0.2, 0.3, and 0.4 μmol/L) were used to affect SH-SY5Y cells. The MTT results showed that pretreatment of SH-SY5Y cells with AS-IV (0.1, 0.2, 0.3, and 0.4 μmol/L) attenuated the damage induced by H2O2 (50 μmol/L, 51.62% cell viability) and increased cell viability to 64.19, 63.48, 65.86, and 65.81%, respectively. Western blot analysis and immunofluorescence staining showed that the protective effects of AS-IV against SH-SY5Y cell damage caused by H2O2 resulted in reduced expression of PSD-95 and increased expression of GAP-43 in comparison with the H2O2 treatment group. The conclusion shows that AS-IV protected SH-SY5Y cells and enhanced their viability under H2O2 stress. AS-IV may facilitate presynaptic and postsynaptic plasticity to exert protective effects against oxidative damage of SH-SY5Y cells.